Functional Analysis of Human Organic Cation Transporter OCT3 (SLC22A3) Polymorphisms - Takeshi Sakata; Naohiko Anzai; Toru Kimura; Daisaku Miura; Toshiyuki Fukutomi; Michio Takeda; Hiroyuki Sakurai; Hitoshi Endou (Elsevier, 2010)
We analyzed the functional properties of five single nucleotide polymorphisms (SNPs) in organic cation transporter OCT3 gene (SLC22A3) resulting in the amino acid changes with a transient expression system. Three SNPs (A116S, T400I, and A439V) exhibited reduced uptake of both [ 3H]histamine and [3H]MPP+, although their protein expressions were detected in the plasma membrane of transfected cells. This study suggests that the OCT3 variants will contribute to interindividual variations leading to the differences in cationic drug disposition as well as certain disease processes such as hypertension, allergic diseases, and neuropsychiatric diseases by the clearance of endogenous organic cations such as biogenic amines. Keywords:: organic cation transporter, single nucleotide polymorphism, histamine